The Performance Impact of Informal and Formal Institutional Differences in Cross-Border Alliances - Sougand Golesorkhi; Roy Mersland; Trond Randøy; Oded Shenkar (International Business Review, 2019)
This study addresses the simultaneous and diverse effects of differences in informal and formal institutions on cross-border alliances' financial performance. We utilize data from 405 microfinance institutions (MFIs), based in 74 developing countries, that have alliances with partners from developed countries. We find that the impact of informal institutional differences between MFIs and their cross-border partners is sigmoid-shaped, with performance first increasing, then declining, before improving again as informal institutional differences grow large. By contrast, formal institutional differences appear to be detrimental to MFIs' performance. Consistent with our prediction, we find that MFIs' cross-border experience moderates both formal and informal institutional effects.
Keywords: 650